Decreased PGE₂ content reduces MMP-1 activity and consequently increases collagen density in human varicose vein. - Ingrid Gomez; Chabha Benyahia; Liliane Louedec; Guy Leséche; Marie-Paule Jacob; Dan Longrois; Xavier Norel (PLoS ONE, 2014)
Varicose veins are elongated and dilated saphenous veins. Despite the high prevalence of this disease, its pathogenesis remains unclear.In this study, we investigated the control of matrix metalloproteinases (MMPs) expression by prostaglandin (PG)E₂ during the vascular wall remodeling of human varicose veins.Varicose (small (SDv) and large diameter (LDv)) and healthy saphenous veins (SV) were obtained after surgery. Microsomal and cytosolic PGE-synthases (mPGES and cPGES) protein and mRNA responsible for PGE₂ metabolism were analyzed in all veins. cPGES protein was absent while its mRNA was weakly expressed. mPGES-2 expression was similar in the different saphenous veins. mPGES-1 mRNA and protein were detected in healthy veins and a significant decrease was found in LDv. Additionally, 15-hydroxyprostaglandin dehydrogenase (15-PGDH), responsible for PGE₂ degradation, was over-expressed in varicose veins. These variations in mPGES-1 and 15-PGDH density account for the decreased PGE₂ level observed in varicose veins. Furthermore, a significant decrease in PGE₂ receptor (EP4) levels was also found in SDv and LDv. Active MMP-1 and total MMP-2 concentrations were significantly decreased in varicose veins while the tissue inhibitors of metalloproteinases (TIMP -1 and -2), were significantly increased, probably explaining the increased collagen content found in LDv. Finally, the MMP/TIMP ratio is restored by exogenous PGE₂ in varicose veins and reduced in presence of an EP4 receptor antagonist in healthy veins.In conclusion, PGE₂ could be responsible for the vascular wall thickening in human varicose veins. This mechanism could be protective, strengthening the vascular wall in order to counteract venous stasis.